Investment–cash flow sensitivity under changing information asymmetry - Chowdhury, Jaideep; Kumar, Raman; Shome, Dilip (Journal of Banking & Finance, 2016)
Empirical studies on whether investments are sensitive to cash flows in imperfect markets often report conflicting results and have been criticized on conceptual and methodological grounds. Our study mitigates some of these problems using a research design that relates changes in investment–cash flow sensitivity to changes in the bid-ask spread measure of information asymmetry surrounding (i) implementation of the Sarbanes-Oxley (SOX) Act and (ii) deregulation of firms in the Transportation, Telecommunication, and Petroleum and Natural Gas industries. Consistent with our hypotheses, we find that information asymmetry decreases following SOX and that there is a corresponding decrease in the investment–cash flow sensitivity, pre- to post-SOX. Further, greater decreases in information asymmetry following SOX are associated with greater decreases in investment–cash flow sensitivity. The results for the deregulation sample are also consistent with our hypothesis, wherein we observe an increase in information asymmetry and corresponding increase in the investment–cash flow sensitivity following deregulation.